SAR Levels for Irradiation by a Crumpled 900 MHz Flexible Diamond Dipole - N. A. Elias; N. A. Samsuri; M. K. A. Rahim; C. J. Panagamuwa; W. Whittow (International Journal of Electrical and Computer Engineering (IJECE), 2017)
In this work, the antenna performance and Specific Absorption Rate (SAR) levels in a homogeneous phantom exposed to 900 MHz flexible diamond dipole antenna are investigated under different crumpling deformation conditions. The numerical simulations of the realistic complex two dimensional crumpling are performed by using Finite Integration Technique (FIT) which is applied in Computer Simulation Technology (CST) Microwave Studio. The validation of results with the industry standard DASY4 robot SAR measurement system is made possible with the use of homogenous phantom model. The 1 g, 10 g and point SAR are enhanced by 28.33 %, 36.75 % and 9.55 % respectively due to the antenna crumpling deformation. The short length ripple investigated in this paper shows the highest relative SAR increment.